Analysis of object-oriented and reuse architectures supported by visual basic and powerbuilder - Lee, Kay Beng. (2008)
Visual basic and powerbuilder are popular rapid development environments for developing client/server database applications. Both products are widely used in the IT industry and claim to implement object orientation and support reusability -of software components.